2020
DOI: 10.1097/iop.0000000000001733
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Multiple Trigeminal Nerve Branches in IgG4-Related Orbital Disease

Abstract: Purpose: To describe the occurrence of multiple trigeminal nerves (TGNs) enlargement in patients with orbital IgG4-related disease. Methods: Retrospective review of MRI findings and medical records of 6 patients (10 orbits) with orbital IgG4-related disease and enlargement of more than 1 TGN. Orbital biopsies were performed in all cases revealing the typical lymphoplasmacytic infiltrate with significant plasma cell positivity for IgG4 (IgG4+/IgG ratio ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…In the present case, separate involvement of perineural optic nerves without perineural spreading and branches of the trigeminal nerves was reported. Perineural spreading between the maxillary nerve and infraorbital nerve was noted in the present case, but not in previous reports [17,20]. No previous IgG4-RON cases mentioned the bilateral maxillary nerves with perineural involvement of infraorbital nerves, which makes the present case exceptional.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…In the present case, separate involvement of perineural optic nerves without perineural spreading and branches of the trigeminal nerves was reported. Perineural spreading between the maxillary nerve and infraorbital nerve was noted in the present case, but not in previous reports [17,20]. No previous IgG4-RON cases mentioned the bilateral maxillary nerves with perineural involvement of infraorbital nerves, which makes the present case exceptional.…”
Section: Discussioncontrasting
confidence: 84%
“…Two studies have reported that the infraorbital nerve was enlarged in approximately 30-38.5% of their IgG4-ROD cases [3,10]. The frontal nerves, supraorbital nerves, infraorbital nerves, lesser palatine nerves, and superior alveolar nerves were the involved sites of the trigeminal nerves in these patients [3,17]. Lesion of the trigeminal nerve branch was particularly unique, and 64% of trigeminal nerve branch lesions observed in Sogabe et al's study were bilateral [3].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The radiological studies of the patients were reviewed by three experienced neuroradiologists blinded to patient history, symptoms, and histopathologic data, using a digital imaging and communications in Medicine (DICOM) viewer system (Horos, https://horosproject.org/) and Enterprise Imaging Agfa HealthCare. The diagnosis of trigeminal perineural disease was based on the classical findings of nerve enlargement or enhancement, obliteration of the fat planes around the nerves and their foramina, and enlargement and/or erosion of foramina, canals and fissures [19][20][21].…”
Section: Imaging Techniquementioning
confidence: 99%
“…In 2011 Katsura et al reported a patient with isolated enlargement of V2 and V3 branches due to an inflammatory process diagnosed as IgG4-RD [9]. Following this report, TGN enlargement, especially of the infraorbital nerve, has been strongly associated with IgG4-RD [10][11][12][13][14][15][16][17][18], Widespread involvement of the TGN is an important feature of IgG4-related disease [19] and less frequently with idiopathic inflammation [20] and lymphoid hyperplasia [16]. Herein we present a new finding of group of patients with orbital disease in whom different TGN divisions were enlarged not only with IgG4-RD, but also with vasculitis and RDD with bilateral perineural enhancement even in unilateral eye disease.…”
Section: Introductionmentioning
confidence: 99%